Yaws' thermophysical properties of chemicals and hydrocarbons - Yaws, Carl L. (Knovel, 2009)
Presents over 7,800 organic and inorganic chemicals, and hydrocarbons. Designed and formatted for field, lab or classroom usage, it provides unparalleled access to invaluable data.